Assessment of integrated rail and bus transport network design: Equity and efficiency perspectives - Mudassar Shafiq; Marco Amorim; António Couto (Transportation Research Interdisciplinary Perspectives)
Recognizing the vital role of public transport (PuT) in accessibility, inclusivity, and quality of life, its planning must balance efficiency with equitable service coverage. This study examines PuT network design, integrating rail and bus services while incorporating equity considerations for a more efficient and socially equitable system. Despite extensive research on PuT network design (PTND), balancing these objectives remains a key challenge in transit planning. This paper presents a methodological framework that integrates PTND with Data Envelopment Analysis (DEA) to design and evaluate multiple PTND scenarios. These scenarios are assessed using equity-based perspectives: potential demand (PD), adjusted demand (AD), and transport needs (TN). The approach identifies efficient designs that maximize service coverage and social equity, addressing varying population demands and needs. The methodology is demonstrated through a case study in the metropolitan area of Porto (AMP), offering policymakers insights into PuT equity implications for the infrastructure planning and decision-making process. Two output-oriented DEA models were developed: one using service coverage adequacy (SCA) as output and another incorporating both SCA and the GINI coefficient (equity) to assess the impact of different equity perspectives on system efficiency. Results indicate that network designs based on AD performed better with higher efficiency scores than PD and TN, suggesting that AD better captures PuT demand needs and supports equitable service distribution. The findings emphasize the need to integrate population equity perspectives and multimodal transport to create more balanced and efficient PuT systems, ensuring fair access to mobility for diverse populations in the region.